Mak nyahs and sex reassignment surgery: a qualitative study from Pahang, Malaysia - Draman, Samsul; Suofeiya, Maliya; Nasarruddin, Muhammad Syaffiq; Zainal, Nur Hamizah; Azeman, Abdul Hakim; Mohd Rus, Razman (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
Introduction: Mak nyahs are locally known male-to-female transgenders in Malaysia. In Western countries, medicalization of transgenderism allows strictly selected patients to undergo sex reassignment surgery. However, a standardized treatment system is not yet available in Malaysia. A number of mak nyahs underwent sex reassignment surgery at their own will. This study aimed to explore mak nyahs’ knowledge and perception on sex reassignment surgery. Materials and Methods: A qualitative research was carried out from 13th July 2016 till 31st August 2016 among 8 adult mak nyahs in Kuantan, Pahang. Snowball sampling was used. Participants who gave verbal consent were interviewed individually and in focus groups. Data obtained was transcribed and used as the primary data source. Results: All informants were Malays and Muslims. They generally had some knowledge about the standard procedures and risks in sex reassignment surgery. All informants expressed their desire to have the surgery, but chose not to. Reasons discouraging them from having the surgery were: i) religion, ii) forbiddance from family, iii) fear of regret, iv) death from surgery, and v) the lack of necessity. Factors driving them to have the surgery: i) more income from sex work, ii) pressure from sex clients, iii) securing a stable relationship, iv) self-satisfaction, and v) hope for a better future. Conclusion: Religion seemed to be the main reason refraining them from undertaking the surgery. Counselling mak nyahs should include the advantages and disadvantages of sexual reassignment surgery. Islamic religious preaching is very important to help reduce high risk behaviours, as well as teaching mak nyahs to cope with challenges in adult life. Further research is necessary to show association between religious knowledge and successful rehabilitation of the mak nyahs’ community.